Development and Characterization of EST-SSR Markers From RNA-Seq Data in Phyllostachys violascens - Cai, Kai (Front Plant Sci, 2019)
Bamboo are woody grass species containing important economic and ecological values. Lei bamboo (Phyllostachys violascens) is a kind of shoot-producing bamboo species with the highest economic yield per unit area. However, identifying different varieties of Lei bamboo based on morphological characteristics is difficult. Microsatellites play an important role in plant identification and genetic diversity analysis and are superior to other molecular markers. In this study, we identified 18,356 expressed sequence tag-simple sequence repeat (EST-SSR) loci in Lei bamboo transcriptome data. A total of 11,264 primer pairs were successfully designed from unigenes of all EST-SSR loci, and 96 primer pairs were randomly selected and synthesized. A total of 54 primer pairs were used for classifying 16 Lei bamboo varieties and 10 different Phyllostachys species. The number of polymorphism alleles among the 54 primer pairs ranged from 3 to 12 for P. violascens varieties and 3 to 20 for Phyllostachys. The phylogenetic tree based on polymorphism alleles successfully distinguished 16 P. violascens varieties and 10 Phyllostachys species. Our study provides abundant EST-SSR resources that are useful for genetic diversity analysis and molecular verification of bamboo and suggests that SSR markers developed from Lei bamboo are more efficient and reliable than ISSR, SRAP or AFLP markers.